Dopamine D2 and D4 receptor heteromerization and its allosteric receptor-receptor interactions - Borroto-Escuela, Dasiel O.; Craenenbroeck, Kathleen Van; Romero-Fernandez, Wilber; Guidolin, Diego; Woods, Amina S.; Rivera, Alicia; Haegeman, Guy; Agnati, Luigi F.; Tarakanov, Alexander O.; Fuxe, Kjell (Elsevier, 2011)
Dopamine D2 and D4 receptors partially codistribute in the dorsal striatum and appear to play a fundamental role in complex behaviors and motor function. The discovery of D2R-D4.xR (D4.2R, D4.4R or D4.7R) heteromers has been made in cellular models using co-immunoprecipitation, in situ Proximity Ligation Assays and BRET1 techniques with the D2R and D4.7R receptors being the least effective in forming heteromers. Allosteric receptor-receptor interactions in D2R-D4.2R and D2R-D4.4 R heteromers were observed using the MAPK assays indicating the existence of an enhancing allosteric receptor-receptor interaction in the corresponding heteromers between the two orthosteric binding sites. The bioinformatic predictions suggest the existence of a basic set of common triplets (ALQ and LRA) in the two participating receptors that may contribute to the receptor-receptor interaction interfaces.
Keywords: Receptores; Dopamina - Receptores; Dopamine D2R receptor; Dopamine D4R receptor; G protein-coupled receptors; Allosteric modulation; Heteroreceptor complexes; Receptor-receptor interactions; Heteromerization